Development of Enzymes in the Cotyledons of Watermelon Seedlings - Kagawa, T. (1973)
Changes in hypocotyl length, cotyledon weight, lipid content, chlorophyll content, and capacity for photosynthesis have been described in seedlings of Citrullus vulgaris, Schrad. (watermelon) growing at 30 C under various light treatments. Corresponding changes in the levels of 19 enzymes in the cotyledons are described, with particular emphasis on enzymes of microbodies, since during normal greening, enzymes of the glyoxysomes are lost and those of leaf peroxisomes appear. In complete darkness enzymes of the glyoxysomes reach a peak at 4 days and decline as the fat is depleted. Enzymes of mitochondria and of glycolytic pathways also peak at 4 to 5 days and either remain unchanged or decline to a lesser extent. Exposure to light at 4 days, when the cotyledons emerge, results in a selectively greater destruction of enzymes of the glyoxylate cycle; chlorophyll synthesis and capacity for photosynthesis increase in parallel, and there is a striking increase in the activities of chloroplast enzymes and in those of the leaf peroxisomes, hydroxypyruvate reductase and glycolate oxidase. The reciprocal changes in enzymes of the glyoxysomes and of leaf peroxisomes can be temporally dissociated, since even after 10 days in darkness, when malate synthetase and isocitrate lyase have reached very low levels, hydroxypyruvate reductase and glycolate oxidase increase strikingly on exposure to light and the cotyledons become photosynthetic. Furthermore, the parallel development of enzymes of leaf peroxisomes and functional chloroplasts is not immutable, since hydroxypyruvate reductase and glycolate oxidase activity can be elicited in darkness following a 5-minute exposure to light at day 4 while chlorophyll does not develop under these conditions.